Modifying Effects of Glucose and Insulin/Insulin-Like Growth Factors on Colon Cancer Cells - Berk, Şeyda; Janssen, Joseph A. M. J. L.; van Koetsveld, Peter M.; Dogan, Fadime; Değerli, Naci; Özcan, Servet; Kelestimur, Fahrettin; Hofland, Leo J. (Frontiers in Oncology, 2021)
There are only a few experimental studies which have investigated effects of glucose alone, and glucose in combination with insulin/insulin-like growth factors (IGF) on the growth of colon cancer. In the present study, we studied in vitro in human colorectal cancer cells originating from four stages of colorectal cancer the effects of glucose, insulin and IGFs on proliferation, cell cycle progression and gene expression of the IGF system. Growth of colon cancer cells originating from an early stage of cancer was glucose-dependent, whereas growth of colorectal cancer cells from late stages was glucose-independent. Stimulatory effects of insulin and IGFs on cell growth were observed only in colon cancer cells originating from late stages of colorectal cancer. The growth stimulatory effects in late stage colorectal cancer cells were accompanied by G2/M arrest and associated with an increased IGF-IR/IGF-II receptor ratio. In conclusion, our in vitro data suggest that the effects of glucose, IGFs and insulin on proliferation differ between colorectal cancer cells from early and late stages. Stimulatory effects of glucose on proliferation appear predominantly present in early stage colorectal cancer cells, while in contrast growth factor-mediated stimulation of cell proliferation is more pronounced in late stage colorectal cancer cells. Moreover, our study suggests that a stringent glucose control is important to control tumor growth in early stages of colorectal cancer, while inhibition of the endocrine actions of the IGFs and insulin become more important in advanced stages of colorectal cancer to restrain growth of colon cancer cells.